Picroscope: low-cost system for simultaneous longitudinal biological imaging - Victoria T. Ly (Nature Portfolio, 2021)
Ly et al. report a multi-well imaging system (the Picroscope) that can perform longitudinal bright-field z-stack imaging for 24 wells simultaneously. They demonstrate its capability by imaging zebrafish embryos, planaria worms, development of Xenopus tropicalis over a 28-h period and embryonic stem cell monolayer and organoids inside an incubator.